Hydrodynamics and mixing characteristics of packed bed biofilm reactor with varying voidage. Issue 1 (August 2021) - Mitra, Praneeti; Sharma, Utkarsh; Magesh Kumar, M.; Samdavid, S.
Abstract: In the present study, hydrodynamics and mixing characteristics of packed bed biofilm reactor are compared by varying voidage using MBBR media and conventional packings. The mixing characteristics are studied using conductivity method. RTD at the entrance and exit of the column is studied and compared for all the packings. The flow approached plug flow with an increase in velocity (3.02 - 5.2 cm/s) and a decrease in voidage of packing (0.92 - MBBR, 0.833 – Raschig rings, 0.45 – Plastic balls).